Development and application of µXRF-CS Cl as a proxy for Holocene drought and hurricane conditions in the Yucatan Aquifer, Mexico - McNeill-Jewer, Chelsi (My University, 2020)
The highly porous karst limestone of the Yucatan Peninsula promotes infiltration of rainwater into the subsurface, where it becomes part of the Yucatan Aquifer. The combination of high subsurface porosity, high evapotranspiration, and seasonal droughts results in relative scarcity of lakes or drinkable water at the surface. The majority of past and present people living on the Yucatan Peninsula have depended on groundwater resources for domestic purposes. Whereas coastal karst aquifers such as the one in the Yucatan Peninsula are important water resources, they are highly vulnerable to climate-related changes such as sea level (SL) rise, increased hurricane intensity and extended droughts. With ongoing development along the eastern coast of the Yucatan Peninsula (Quintana Roo), predicted increases in storm intensity, and rising population and potential pollutant output, it has become imperative to study the seasonal and long-term effects of climate and human activity on the Yucatan Aquifer. Like many coastal karst aquifers, the Yucatan Aquifer is stratified according to density, with the Meteoric Water Mass (MeWM) flowing towards the coast on top, and the Marine Water Mass (MaWM) flowing inland on the bottom. The current basis of our knowledge about how the two water masses interact has been from short-term instrumental monitoring and numerical modelling, which is useful for understanding straightforward relationships between salinity, precipitation and temperature across the two water masses and have paved the way for more complex analyses to be completed using the simple principles to guide geochemical studies of sediment within the systems. Generally, sediment cores have been analysed discretely using various methods including grain size analysis, micropaleontology, WD-XRF, and others, however the recent rise of µXRF Core Scanning provides a quicker, more cost effective and higher-resolution method for studying climate-related patterns in sediment cores. This thesis outlines and provides robust evidence for three new methods of using µXRF-CS to determine past and present climatological changes and their relationship to sediment elemental counts. We provide the first outline of the seasonal and spatial controls of geochemical changes in sedimentation in a coastal cave system (Yax Chen), using four years of in situ sediment collection. We then provide the first calibrated record of past salinity based on Cl counts within sediment cores taken from shallow lakes. Although instrumental monitoring has provided evidence that the aquifer is impacted by modern wet and dry periods, the effect of past climate on the aquifer has not been investigated. We provide the first record of water-column mixing at three locations within coastal Quintana Roo. This demonstrates that there has been a long-term climate impacts to coastal Yucatan Peninsula groundwater, which may be scaled to other karst islands and provides evidence that increased hurricane frequency and/or magnitude could change the baseline salinity of the fresh MeWM.
Keywords: yucatan peninsula, cave systems, sedimentology, paleoclimatology, paleosalinity